Debt Dynamics in Emerging and Developing Economies : Is R-G a Red Herring? - Moreno Badia, Marialuz (IMF Working Papers; Working Paper ;, 2021)
In the wake of the COVID-19 pandemic, debt levels in emerging and developing economies have surged raising concerns about fiscal sustainability. Historically, negative interest-growth differentials in these countries have played a debt-stabilizing role. But is this enough to prevent countries from falling into debt distress? Drawing from a sample of 150 emerging and developing economies going back to the 1970s, we find that interest-growth differentials have remained relatively low, dampening debt increases in the run up to a crisis. But in the face of persistent primary deficits, debt service tends to rise abruptly-particularly in emerging markets-and a fiscal crisis ensues. There is also evidence that a large part of the debt build-up around crises stems from valuation effects associated with external debt and the materialization of contingent liabilities. These findings underscore that, though not necessarily a red-herring, low interest-growth differentials cannot fully offset the deleterious effects of large fiscal deficits, forex exposures, or hidden debts.